Nursing home nurses' turnover intention: A systematic review - Jiyeon Lee (Wiley, 2022)
Abstract Aim This review aimed to examine and describe the published research on nursing home (NH) nurses' turnover intentions in their workplace. Design This study is a systematic review following PRISMA guidelines. Methods An electronic search was conducted for English and Korean articles to identify research studies published between 2009-2019 using CINAHL, PubMed, Cochrane Library, PsycINFO, RISS, and DBpia. Results A total of six studies met the inclusion criteria and revealed NH nurses' turnover intentions. The factors influencing NH nurses' turnover intentions were identified and classified as individual and organizational factors. Among the various factors above, this study found that job satisfaction was the most influential factor in nurses' turnover intentions. Therefore, further efforts are required to increase NH nurses' job satisfaction to decrease turnover intention.